Analisis Potensi Kesiapsiagaan Masyarakat dalam Menghadapi Bencana Banjir - Sri Wahyuni Adriani; Zuhrotul Eka Yulis Anggraeni; Nabil Mumtaz Hidayat; Faridatul Gufroniah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  To analyze the potential for community preparedness in dealing with flood disasters. Methods:  This research was correlational study with a cross sectional approach. This research was conducted in the Suci Village area of Panti Sub-district on the basis that Panti District has been hit by floods, and Suci Village was an area that was quite severely affected by floods. The population in this study were the family, especially families who have family members belonging to vulnerable groups such as pregnant women, infants and toddlers, disabled, and the elderly totaling 312 families. Samples were taken with a stratified random sampling of 120 sampel. Data analysis used ordinal regression.Results:  The results show that the majority of the community's preparedness in dealing with flood disasters was not ready and the factors that influence community preparedness in dealing with disasters were knowledge and attitude, emergency planning, disaster warning system, and resource mobilization capacity.Conclusion:  Improve community preparedness in dealing with flood disasters by looking at the community potential was very important to do.